(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Historical drama occupies a significant place in Turkish literature because it serves not only as a literary genre but also as a means of preserving collective memory and strengthening national identity. Among contemporary Turkish playwrights, Turgut Özakman stands out for his ability to transform historical events into compelling dramatic narratives without sacrificing historical authenticity. His play Çanakkale, included in the trilogy Üç Destan (2002), presents one of the most influential theatrical interpretations of the Gallipoli Campaign. Rather than merely reconstructing military events, Özakman combines documentary evidence, historical facts, and dramatic imagination to portray the moral, psychological, and emotional dimensions of the struggle. This study examines how historical reality is represented in Çanakkale through dramaturgical techniques, narrative structure, characterization, and symbolic language.